Mendelian Randomization Analysis Reveals a Causal Effect of Urinary Sodium/Urinary Creatinine Ratio on Kidney Function in Europeans - Zhang, Yue-miao; Zheng, Jie; Gaunt, Tom R.; Zhang, Hong (Frontiers in Bioengineering and Biotechnology, 2020)
Salt restriction was recommended in clinical practice guideline for chronic kidney disease (CKD) treatment, but its effect on kidney outcomes remains conflicting. We aimed to test the causal effect of salt intake, measured as urinary sodium/creatinine ratio (UNa+/UCr) estimated from spot urine, on renal function using two-sample Mendelian randomization (MR). Genetic instruments for UNa+/UCr were derived from a recent genome-wide association study of 109,178 European-descent individuals in the UK Biobank. Kidney outcomes were estimated glomerular filtration rate (eGFR) (N= 133,413) and CKD (eGFR < 60 ml/min/1.73m2, N-cases= 12,385; N-controls= 104,780) from the CKDGen consortium. All MR and sensitivity analyses were conducted using MR-Base. MR revealed a causal effect of UNa+/UCr on higher eGFR (β = 0.22, unit change in log mL/min/1.73 m2 per increase of UNa+/UCr ratio; 95% confidence interval [CI] = 0.11 to 0.32, P = 6.66 × 10-5). UNa+/UCr ratio conferred a protective effect against CKD risk (OR = 0.22, 95% CI = 0.07 to 0.72, P = 1.20 × 10-2). The MR findings were confirmed by MR-Egger regression, weighted median MR and mode estimate MR, with less evidence of existing of horizontal pleiotropy. The average 24-hour sodium excretion was estimated to be approximately 2.6 g per day for women and 3.7 g per day for men. This study provides evidence of a beneficial effect of sodium excretion, well above the recommendation of <2 g per day of sodium, on kidney function. Clinical trials are warranted to evaluate the sodium restriction target on kidney function.